Improved shear design rules of cold-formed steel beams. (15th September 2015) - Keerthan, Poologanathan; Mahendran, Mahen
Highlights: Investigated the shear behaviour of open and hollow flange cold-formed steel beams. Current shear design rules are very conservative. Developed equations for shear buckling coefficient of open and hollow flange beams. Proposed generalised and improved shear design rules for cold-formed steel beams. Developed direct strength method for shear capacities of open and hollow flange beams. Abstract: Light gauge cold-formed steel sections have been developed as more economical building solutions to the alternative heavier hot-rolled sections in the commercial and residential markets. Cold-formed lipped channel beams (LCB), LiteSteel Beams (LSB) and Triangular Hollow Flange Beams (THFB) are commonly used as flexural members such as floor joists and bearers while Rectangular Hollow Flange Beams (RHFB) are used in small scale housing developments through to large building structures. However, their shear capacities are determined based on conservative design rules. For the shear design of cold-formed steel beams, their elastic shear buckling strength and the potential post-buckling strength must be determined accurately. Hence experimental and numerical studies were conducted to investigate the shear behaviour and strength of LCBs, LSBs, THFBs and RHFBs. Improved shear design rules including the direct strength method (DSM) based design equations were developed to determine the ultimate shear capacities of these open and hollow flange steel beams. An improved equation for the higher elastic shear buckling coefficient of cold-formed steel beams was proposed based on finite element analysis results and included in the design equations. A new post-buckling coefficient was also introduced in the design equations to include the available post-buckling strength of cold-formed steel beams. This paper presents the details of this study on cold-formed steel beams subject to shear, and the results. It proposes generalised and improved shear design rules that can be used for any type of cold-formed steel beam.